Study of causative agent & their susceptibility pattern in sepsis in young infants below 3 months of age - Chandran, Rabindran; Parakh, Hemant; N. Iyer, Ranganathan; Rao, Jangam Rekha (International Journal of Medical Research and Review, 2015)
Introduction: Pathogens causing blood stream infections and their antibiotic susceptibility patterns constantly change over time & it is essential to monitor the epidemiology of infections to design appropriate antibiotic policy. Methodology: Blood culture reports of Children below 3 months of age admitted to our hospital over a period of 4 years were analysed to find the causative agents of sepsis & their antibiotic susceptibilities. All data were collected in validated preformatted proforma sheet & analysed using appropriate statistical methods. Results: Among 1401 blood cultures, culture positive growth was observed in 226 cases (16.1 %). In our study, Klebsiella pneumoniae was the commonest isolated in 23.4 % of blood cultures. Acinetobacter baumanii was the next commonest organism isolated in 13.7 % followed by MRSA growth in 11.9 %, MSSA in 4.8 %, E.coli in 8.8 %, Enterococcus faecalis in 7.5 %, B.cepacia in 6.6 %, P. aeruginosa in 5.3% & Enterobacter in 4.4 % of blood cultures. About 49% of K. pneumoniae were susceptible to Carbapenam & 60% of E.coli were susceptible to Amikacin & Tobramycin. All Enterobacter were sensitive to Imipenam, Meropenam, Ertapenam & Amikacin & 77% of A.baumanii were sensitive to Carbapenam. Yeasts were isolated in 8.4 %, the commonest being Candida tropicalis. Conclusion: It is essential to closely monitor the bacterial flora and their antibiotic sensitivity pattern to evolve rational antibiotic policy which is suitable for each unit. Guidelines on the reduction of emergence of drug resistance must be provided and instituted within the units.